Refrigeration: home and commercial - Miller, Rex, 1929-2019 (Audel Technical Trades Series., 2004)
Know how to put a chill in the airHere at last is a reference manual devoted exclusively to refrigeration, both home and commercial. Beginning with the essential physics and math, it provides a complete course in maintaining, troubleshooting, and repairing both new and vintage refrigeration systems for home and light industry. You'll find the answers you need, whether you're a student, apprentice, cost-conscious homeowner, or skilled technician.* Know how different types of refrigerants are used and how to handle them safely* Perform routine maintenance on various types of comp.